DOI: 10.58837/chula.the.2021.179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ferulic acid and UV curing on properties of soy protein film

Md Shakil

Abstract: The objective of this study was to explore the effect of UV-C curing on the properties of ferulic acid-added soy protein film. The films were fabricated from soy protein isolate and added with 1.5% ferulic acid. UV-C radiation was applied at four different doses (0.32, 1.56, 4.00, 12.00 J/cm2) to either preformed film or film-forming solution. The mechanical, physicochemical, and morphological properties of the film samples were investigated. Ferulic acid addition and UV-C curing at 0.32 J/cm2 posed a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Film samples were prepared according to the method described earlier (Shakil & Mahawanich, 2022) with some modifications. Soy protein film without heat curing treatment was used as a control.…”
Section: Effect Of Heat Curing On Properties Of Soy Protein Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…Film samples were prepared according to the method described earlier (Shakil & Mahawanich, 2022) with some modifications. Soy protein film without heat curing treatment was used as a control.…”
Section: Effect Of Heat Curing On Properties Of Soy Protein Filmmentioning
confidence: 99%
“…The filmforming solution exposed to the highest UV dose yielded a film with significantly improved tensile strength, puncture strength, puncture deformation, with decreasing water solubility as compared to the untreated control. Shakil & Mahawanich (2022) assessed the impact of UV-C treatment (0.32, 1.56, 4.00, 12.00 J/cm 2 ) on either pre-formed film or film-forming solution of ferulic acid-fortified soy protein film. It was revealed that the films treated with the highest radiation dose displayed an increase in both tensile strength and elongation at break as compared to the untreated controls.…”
Section: Introductionmentioning
confidence: 99%